Community of Practice: A flexible construct for understanding SME networking roles in the Irish artisan cheese sector. (November 2018) - Crowley, Caren; McAdam, Maura; Cunningham, James A.; Hilliard, Rachel
Abstract: Networking is generally seen as an important mechanism for small scale and rural enterprises to overcome their relative disadvantage by leveraging knowledge and resources. Communities of practice (CoP) are a type of network where close relationships develop around a shared identity and understanding. However, a commonly occurring critique of the CoP literature is that little attention is paid to asymmetric and unequal relationships and knowledge access among members. Thus, a gap remains regarding differences in the ability and willingness of members to engage with and develop the CoP, and, as a result, the different networking roles that emerge. In order to address this research gap, we present a full population, country-level study set in the Irish artisan cheese sector. We adopted a two-stage research design consisting of social network analysis (SNA) and 51 in-depth qualitative interviews. In this particular CoP, we find that membership is not negotiated in a uniform manner and that differences in participation can be identified and categorised by a focus on the intersection of owner-managers' participation identity and firm network positions. Building on this, we develop an original role typology depicting five distinct networking roles and examine how these different network identities relate to firm network positions and roles. It is posited that this typology can act as a sense-making tool for researchers and practitioners by which to diagnose and understand variation in small firm horizontal peer networking behaviour, particularly within the artisan based agri-food sector. Highlights: First, we respond to calls for research into the variation in small firm networking within a single industry sector. Second, we provide a more nuanced understanding of participation identities negotiated within a Community of Practice. Third, we examine how participation identities relate to firm network position to develop a typology of networking roles. Fourth, we contribute to research on artisan SMEs, specifically 'how' and 'why' owner-managers engage in peer networking. Finally, for practitioners' this role typology provides a flexible framework to diagnose the informal governance system.